The shift of expenditure of medical service for diagnosis and treatment of colorectal cancer from 2005 to 2014: a hospital-based retrospective survey in Guangxi - Liang, Wenjie; Lu, Haiyan; Huang, Kaiyong; Yang, Li (Frontiers in Public Health, 2025)
PurposeMedical expenditures for colorectal cancer (CRC) in China have risen substantially, with significant geographic disparities. This study aimed to comprehensively assess the level, temporal trends, and influencing factors of medical expenditures per patient, per clinical visit, and per day among CRC patients in Guangxi from 2005 to 2014.MethodsA retrospective, hospital-based survey was conducted in 2015 at a Class A tertiary cancer hospital in Nanning, Guangxi. The study included patients newly diagnosed with primary CRC between January 1, 2005, and December 31, 2014. Data on demographics, clinical characteristics, and detailed medical costs were extracted from electronic medical records. All expenditure values were adjusted for inflation to 2011 Chinese Yuan (CNY) using China’s healthcare-specific Consumer Price Index. Statistical analyses included descriptive statistics, non-parametric tests, Spearman correlation, and binary logistic regression.ResultsA total of 1,029 eligible CRC patients were analyzed. The median medical expenditures were CNY 50,540 per patient, CNY 24,618 per clinical visit/admission, and CNY 1,410 per day. From 2005 to 2014, these expenditures increased by factors of 1.63, 1.13, and 2.44, respectively, with annual growth rates of 5.59, 1.41, and 10.42%. Notably, the annual per-patient medical expense was 2.2 to 3.3 times the per-capita GDP of Guangxi during the same period. Drug fees constituted the largest proportion of total costs (61.22%), followed by laboratory test fees (12.27%) and inspection fees (7.58%). Subgroup and regression analyses revealed that treatment regimen, number of clinical visits/admissions, and length of hospitalization were significant factors associated with higher costs. A high proportion of patients (59.87%) were diagnosed at an advanced stage (III-IV).ConclusionMedical expenditures for CRC diagnosis and treatment in Guangxi during the study period were substantial and increased rapidly, imposing a significant economic burden. The cost structure was heavily dominated by pharmaceutical expenses. The findings underscore the need for policies promoting early detection and efficient resource allocation. This study provides a critical baseline for evaluating the impact of subsequent healthcare reforms and informs future health economic research in Guangxi and similar regions.